The Enhancement of Creative Thinking Skill Using Creative Problem Solving Learning Model - Luthfia, Syarifatul (Yayasan Nurul Yakin Bunga Tanjung, 2024)
This study aims to determine students' creative thinking skills by applying the creative problem-solving (CPS) model to electricity material with fluency, flexibility, originality, and elaboration indicators. The subjects of this research are 27 sixth-grade students in Al-Irsyad Banyuwangi Elementary School. This research was conducted through classroom action research consisting of two cycles. Data were collected using essay test instruments with scores of 1 to 4. The results of the diagnostic assessment of creative thinking were 43.17. After applying the CPS model, the results showed that the average fluency was 52.78 (cycle I) and 58.80 (cycle II), flexibility was 48.15 (cycle I) and 64.35 (cycle II), originality was 41.67 (cycle I) and 57.87 (cycle II), and elaboration was 62.96 (cycle I) and 68.98 (cycle II). The class average score increased to 51.39 and again to 62.5 in cycle II. Based on these data, applying CPS in learning electricity can improve students' creative thinking skills.